External Ophthalmomyiasis Caused by a Rare Infesting Larva, Sarcophaga argyrostoma. (22nd December 2013) - Graffi, Shmuel; Peretz, Avi; Wilamowski, Amos; Schnur, Heather; Akad, Fouad; Naftali, Modi
Abstract : Purpose . External ophthalmomyiasis (EO) is caused by infesting larvae belonging to various species of flies. Most documented cases result from sheep ( Oestrus ovis ) and Russian ( Rhinoestrus purpureus ) botfly larvae, but we recently discovered a rare case of EO caused by flesh fly ( Sarcophaga argyrostoma ) larvae. Here, we report the case of a patient with EO who had been hospitalized and sedated for 1 week because of unrelated pneumonia. Methods . Case report. Results . A total of 32 larvae were removed from the adnexae of both eyes. Larvae identification was confirmed through DNA analysis. Treatment with topical tobramycin resulted in complete resolution of EO. Conclusion . EO can be caused by S. argyrostoma, and the elderly and debilitated may require extra ocular protection against flies during sedation.